THE RELATION OF PERSONAL HYGIENE WITH BODY APPEARANCE AT THE OLD AGE PEOPLE IN SEPE VILLAGE LAGE SUB-DISTRIC POSO REGENCY - Kadar Ramadhan; Iin Sabrina K.A (Jurnal Kesehatan Prima, 2016)
Abstract : Background: the more people’s age, they will experience a decrease, especially in terms of  physical ability. This problem causes the appearance of interference in fulfilling their life needs, especially personal hygiene needs. The superior personal hygiene will affect to the enhancement of individual body image. In contrast, the lack of personal hygiene will certainly affect to the decline of person's body image. The decline of personal hygiene for the old people can affect to self-image and causes them to feel dissatisfactory in appearance. The aim of the research: Knowing a relationship between personal hygiene with body image for the old age people in Sepe village Lage Sub-district Poso Regency. Methods: the research design was observational analytic with cross sectional study. The population was the old age people around 60-90 years old as many as 102 people. Total sample was 80 people, using random sampling techniques. The data analyses used Chi - Square test with value α 0.05. The result of study: the superior personal hygiene was 31.2%, the sufficient personal hygiene was 61.2 %, and 7.5% belonging to less personal hygne. Meanwhile, positive body image was 51.2% and negative body image was 48.8%. 100% of respondents who have a lack personal hygiene have a negative body image, while 92% of respondents who have superior personal hygienenya have a positive body image. Conclusion: there is a relationship between personal hygiene with body image for the old age people in Sepe Village Lage Sub-District Poso Regency. Suggestion: it is expected to the old age people’s family to able to give better attention to them. Besides, for the old age people are expected to able to develop their ability in maintaining themselves and their health.